Crisis in history or crisis historiography - Janet L. Roitman (Finance and Society, 2020)
History in Financial Times sheds light on the historiography of contemporary finance. But there is a tension in the book that is inescapable: between the production of crisis historiography, on the one hand, and the practice of the concept of crisis, on the other. There is, in other words, a barely articulated distinction between crisis as a "metahistorical force" and crisis as a "peculiar, naturalist" category.
Keywords: 300